Implementasi LoRa pada Monitoring Tempat Pembakaran Sampah berbasis Website: Implementation of LoRa in a Website – Based Waste Incinerator site Monitoring System - Muhammad Raehan Maulana; Hafiz Muhardi; Midyanti, Dwi Marisa (Computer Science and Information Technology, 2026)
Waste accumulation is a common problem caused by low public awareness of waste management and suboptimal waste handling by sanitation workers. Waste incineration can serve as a solution, but it has the potential to cause undesirable consequences if not properly supervised; therefore, a monitoring system capable of tracking the waste incineration process in real-time is necessary. With the rapid advancement of technology, wireless technology can be utilized to address this issue. However, most wireless technologies still rely on internet networks, making them less effective in areas with limited internet connectivity. Therefore, this study proposes the use of LoRa technology as a solution for data transmission without reliance on an internet network. The developed system can monitor waste incineration sites using MQ-2 sensors and flame sensors in real-time via a website, utilizing the LoRa SX1278 data transmission system. Implementation results show that the monitoring system can detect residual smoke and fire from waste incineration sites and monitor them up to a distance of 150 meters. Signal quality in LoRa SX1278 transmission is expressed in RSSI (Received Signal Strength Indicator) units, with an “excellent” signal category achieved up to a distance of 40 meters in the tests conducted.